Challenges of Applying Agile Principles and Values to IT Project Management - Carmen Novac; Raluca Ciochina (Journal of Entrepreneurship, Management and Innovation)

(untitled)
The theoretical part of this paper focuses on a macro-analysis of the Agile system philosophy, one of the most popular project management frameworks from the software industry. The second part of the paper consists of a case study analyzing the practices of the Agile framework within a corporation at the level of software production. As far as methodology is concerned, the qualitative research was conducted through a case study of a team in a distributed context (“cross-team”). Participant observation was used as a tool for collecting the data about the individuals and the processes within the teams. The purpose of the research was to analyze the current state of implementation, the benefits and challenges of using the Agile project management framework and also the needs of software development teams within a multinational company. At the same time, the paper analyzes the redefinition of roles by applying the Agile project management framework within the distributed teamwork organization. The research aims to identify the underlying reasons for the choice of the Agile type of management instead of Lean management within the software development industry, focusing on the level of implementation of the Agile/Scrum methodology and principles in distributed teams.